Changes in health professionals' knowledge, attitudes and practice following provision of educational resources about prevention of prenatal alcohol exposure and fetal alcohol spectrum disorder - Payne, J.; France, K.; Henley, N.; D'antoine, Heather; Bartu, Anne; O'Leary, C.; Elliott, E.; Bower, C. (Wiley-Blackwell Publishing Ltd., 2011)
We provided health professionals in Western Australia (WA) with educational resources about prevention of prenatal alcohol exposure and fetal alcohol spectrum disorder and assessed changes in their knowledge, attitudes and practice concerning fetal alcohol syndrome (FAS) and alcohol consumption in pregnancy. Following our 2002 survey of health professionals in WA, we developed and distributed educational resources to 3348 health professionals in WA in 2007. Six months later we surveyed 1483 of these health professionals. Prevalence rate ratios [PRR] and 95% confidence intervals [CI] were calculated to compare 2007 results with results from the 2002 survey. Of the 1001 responding health professionals, 69.8% had seen the educational resources; of these 77.1% have used them and 48.5% said the resources had assisted them to change their practice or their intention to change their practice.Compared with 2002, there was an increase in the proportion who knew all the essential features of FAS from 11.7% to 15.8% [PRR 1.35; 95% CI 1.09, 1.67] and had diagnosed FAS, from 4.8% to 7.3% [PRR 1.52; 95% CI 1.08, 2.13]. In 2007, 98.1% of health professionals stated they would advise pregnant women to consider not drinking at all or advise them that no alcohol in pregnancy is the safest choice. Health professionals surveyed in 2007 have increased their knowledge, changed their attitudes and practice about FAS, and altered the advice they give to pregnant women about alcohol consumption since our survey in 2002. It is essential that we build on this change and continue to support health professionals' knowledge, attitudes and practice about the prevention of prenatal alcohol exposure and fetal alcohol spectrum disorder.